A review of Air-Core coil sensors in surface geophysical exploration. (January 2022) - Lin, Tingting; Zhou, Kun; Cao, Yiming; Wan, Ling
Highlights: Air-core coil sensors are important magnetic measurement tools for surface geophysical technology. Detailed design process of induction coil and air-core coil sensor is presented. Optimization methods for air-core coil sensors in TEM and SNMR applications are reviewed. Research prospects of sensor technology in surface geophysical exploration are examined. Abstract: In the field of surface geophysical detection, electromagnetic technologies represented by transient electromagnetic methods (TEMs) and surface nuclear magnetic resonance (SNMR) use air-core coil sensors as magnetic detection devices because of their high sensitivity, simple fabrication, robustness, and low cost. To clarify the application of air-core coil sensors in these fields, we review the design process and research directions of these devices. First, we introduce the detection principles and parameters of induction coils. Second, we summarize the structure, equivalent model, amplitude–frequency characteristics, and noise level of air-core coil sensors. Third, the characteristics of the air-core coil sensors used in TEMs and SNMR are introduced respectively, and the optimization of parameters such as the noise level, sensitivity, and size of these magnetic detection devices according to actual application conditions is then discussed in detail. Finally, we propose directions for future research based on existing problems in the use of air-core coil sensors, and provide ideas for their further development in geophysical detection.